Does FDI Work as a Channel for R&D Spillovers? Evidence Based on Swedish Data - Henrik Braconier; Karolina Ekholm; Karen Helene Midelfart Knarvik (The Research Institute of Industrial Economics (IUI), 2001)
Multinational enterprises (MNEs) are important in transmitting technology across national borders. Not only do they allow for transfer of technology within the firm, but it is also believed that they are important channels for international R&D spillovers as well. This paper analyzes empirically whether inward and outward foreign direct investment (FDI) work as channels for international R&D spillovers. We utilize firm-level as well as industry-level data for Swedish manufacturing in the analysis. We find no evidence of FDI-related R&D spillovers - neither at the firm-level nor at the industry-level in Swedish manufacturing. The only variable that consistently affects total factor productivity is own investment in R&D.
Keywords: F23; O32; O33; 330; Multinational enterprises; Foreign direct investment; Spillovers; Research and development; Spillover-Effekt; Industrieforschung; Multinationales Unternehmen; Industrie; Schweden